Building Digital Skills and Introducing AI for Santri Through a Training Program at the As-Sunniyah Islamic Boarding school in Kencong Jember - Mutmainah , Siti; Khurin’In Ratnasari; Ratnasari, Dukan Jauhari F (International Journal of Community Service Learning, 2024)
The lack of people who know about the use of AI in Islamic boarding schools means that students do not have the instinct to explore the vast digital world, which is very beneficial for life. This research aims to analyze the role of training and mentoring programs on digital skills and the introduction of AI for students at Islamic boarding schools. This research uses the PAR (Participatory Action Research) method through collaborative steps involving discussion, dialogue, and active participation from all related parties. The subjects involved in the research were Islamic boarding school students. Data collection methods were carried out by observation and interviews. Data analysis was carried out descriptively. This research shows that the empowerment program through training effectively improves digital skills and introduces AI to Islamic boarding school students. Through this digital skills empowerment and development program, they provide knowledge and skills to see various learning opportunities around them and be creative in utilizing everything in the digital world to make everything easier.